Influence of microwave disinfection on the dimensional stability of intact and relined acrylic resin denture bases - Seo, Rosangela Seiko; Vergani, Carlos Eduardo [UNESP]; Pavarina, Ana Claudia [UNESP]; Compagnoni, Marco Antonio [UNESP]; Machado, Ana Lucia [UNESP] (Elsevier B.V., 2007)
Statement of problem. Microwave irradiation has been suggested as a method to disinfect denture bases. However, the effect of microwave heating on the dimensional stability of the relined denture bases is unknown.Purpose. The purpose of this study was to evaluate the dimensional stability of intact and relined acrylic resin denture bases after microwave disinfection.Material and methods. A standard brass cast simulating an edentulous maxillary arch was machined and used to fabricate 2- and 4-mm-thick denture bases (n=200), which were processed with heat-polymerized acrylic resin (Lucitone 550). The 2-mm thick-specimens (n=160) were relined with 2 mm of autopolymerizing resin (Tokuso Rebase Fast, Ufi Gel Hard, Kooliner, or New Truliner). Distances between 5 removable pins on the standard brass cast were measured with a Nikon optical comparator, and the area (mm(2)) formed by the distance between 5 pins was calculated and served as baseline. During fabrication, the pins were transferred to the intaglio surface of the specimens. Differences between the baseline area and those subsequently determined for the specimens were used to calculate the percent dimensional changes. The intact and relined denture bases were divided into 4 groups (n=10) and evaluated after: polymerization (control group P); 1 cycle of microwave disinfection (MW); daily microwave disinfection for 7 days (control group MW7); water storage for 7 days (WS7). Microwave irradiation was performed for 6 minutes at 650 W. Data were analyzed using 2-way ANOVA followed by Tukey's test (alpha=.05).Results. Intact specimens and those relined with Kooliner and New Truliner showed increased shrinkage after 1 (P=.05, .018, and .001, respectively) and 7 (P <.001, .003, and <.001, respectively) cycles of microwave disinfection. With the exception of specimens relined with Kooliner, intact specimens showed greater shrinkage than the relined specimens after 7 cycles of microwave disinfection.Conclusions. Microwave disinfection produced increased shrinkage of intact specimens and those relined with New Truliner and Kooliner.